The Energy Density Gap of Harmonic Maps between Finsler Manifolds. (1st August 2011) - Han, Jingwei; Yu, Yao-yong; Yu, Jing
Abstract : We study the energy density function of nondegenerate smooth maps with vanishing tension field between two real Finsler manifolds. Firstly, we get a variation formula of energy density function by using moving frame. With this formula, we obtain a rigidity theorem of nondegenerate map with vanishing tension field from the Finsler manifold to the Berwald manifold.